2023
DOI: 10.1080/21645515.2023.2202125
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete immunization and its determinants among children in Africa: Systematic review and meta-analysis

Abstract: Immunization is one of the most cost-effective measures to prevent morbidity and mortality in children. Therefore, the purpose of this systematic review and meta-analysis was to determine the pooled prevalence of incomplete immunization among children in Africa as well as its determinants. PubMed, Google Scholar, Scopus, Science Direct, and online institutional repository homes were searched. Studies published within English language, with full text available for searching, and studies conducted in Africa were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
1
1
0
Order By: Relevance
“…The global coverage of DTP3 decreased from 86% in 2019 to 83% in 2020 [ 51 , 88 ]. Similar declines had been found in Africa and Asia [ 44 , 89 ]. In contrast to other regions, Europe experienced a minor reduction in vaccination coverage.…”
Section: Discussionsupporting
confidence: 82%
“…The global coverage of DTP3 decreased from 86% in 2019 to 83% in 2020 [ 51 , 88 ]. Similar declines had been found in Africa and Asia [ 44 , 89 ]. In contrast to other regions, Europe experienced a minor reduction in vaccination coverage.…”
Section: Discussionsupporting
confidence: 82%
“…A recent meta-analysis has found that the prevalence of incomplete immunization (failing to receive any vaccination doses) in Africa was 35.5%. The main risk factors were home birth, rural residence, lack of antenatal care visits, knowledge of immunizations, and maternal illiteracy [ 47 ].…”
Section: Discussionmentioning
confidence: 99%